An overview of surgery-first orthognathic approach: History, indications and limitations, protocols, and dentoskeletal stability - Atefe Ahmadvand; Shiva Alavi; Saeed Hasani Mehraban (Wolters Kluwer Medknow Publications, 2021)
The most common orthognathic surgery approach consists of three steps: presurgical orthodontic treatment, surgery, and postsurgical orthodontic treatment. Despite its advantages, this technique has some disadvantages, too, including a long treatment period, problems in mastication and articulation, temporary worsening of the patient's appearance, and psychological problems for the patient. The introduction of the surgery-first orthognathic approach has been an attempt to overcome these problems. In this article, we wish to provide a comprehensive overview on this approach. In this approach, which consists of surgery without orthodontic preparation and a short period of orthodontic treatment after it, the overall duration of treatment decreases and the patient's appearance improves. The skeletal anchorage, placed at the time of surgery, can be used to facilitate tooth movements after surgery. Despite the advantages of this technique, it is associated with some limitations; in particular, occlusion cannot have a guiding role during surgery. Therefore, correct diagnosis, prediction of the outcomes, and simulating correction with the model setup are of crucial importance. The surgeon's knowledge and expertise have a significant role in this respect.